Electrocardiographic left venticular hypertrophy criteria and ambulatory blood pressure monitoring parameters in hypertension - Tuan, Pham Quang; Thi, Tran Thi Ha; Minh, Huynh Van; Thanh, Pham Dinh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: Left ventricular hypertrophy in hypertensive patients is an early complication, related to blood pressure control and the appearance of arrhythmias, especially atrial fibrillation, once it appears, the patient has been stratified to a high cardiovascular risk. 24 - hour ambulatory blood pressure predicted cardiovascular risk and target organ damage stronger than office blood pressure. However, in Vietnam, there are not many assessment of left ventricular hypertrophy detected on electrocardiogram. Therefore, we conducted our study, studying left ventricular hypertrophy on electrocardiogram and some parameters of 24-hour ambulatory blood pressure in hypertensive patients. Methods: 101 patients admitted to the Department of Cardiology, Hue Central Hospital, diagnosed with hypertension according to the Vietnam Society of Hypertension 2022 and previously treated for hypertension. Electrocardiogram and 24-hour ambulatory blood pressure monitoring were performed. The study method was a cross-sectional descriptive study with comparison. Results: In the hypertensive group with/without left ventricular hypertrophy on electrocardiogram, the rate of morning surge was 73.33% vs. 46.48% (p < 0.05). Hypertension with morning surge increased the risk of left ventricular hypertrophy on electrocardiogram by 3.17 times compared with hypertension without morning surge (p < 0.05) and increased the risk of increased Sokolow - Lyon voltage index on electrocardiogram by 9.03 times (p < 0.05). There was a weak positive correlation between 24-hour mean SBP and day mean SBP with the Cornell index and the GubnerUngerleider index with p < 0.05. There was a weak positive correlation between the Cornell index and the GubnerUngerleider index with p < 0.05. There was a weak positive correlation between the night-time mean SBP and nighttime mean DBP with the Cornell index with p < 0.05. Conclusion: 24 - hour ambulatory blood pressure parameters predict the appearance of left ventricular hypertrophy detected on electrocardiogram, as well as provide information to treat hypertension.